Investigations on Stacked Aperture Coupled Fractal Microstrip Antennas for Wireless Communication Applications - Kumari, Laxmi (My University, 2018)
The wireless industry has undergone an advanced technical revolution in present era. Antenna, the most important component in the wireless systems requires versatility and efficiency in order to support the demands of current wireless communication scenario. Apart from the demand for small-size antennas, the advanced wireless communication systems prefer multiband antennas, so as to cover maximum applications with a single antenna. Fractal microstrip antennas (MSAs) play the principle part by fulfilling such wireless signalling requirements. Fractal MSAs exhibit non-integral dimensional configurations, and their spacefilling capabilities can be utilised for miniaturizing antenna size, and their characteristics of self-similarity in geometry result in the antennas having more number of resonant frequencies. Usually, fractal antennas doesn't need any matching components to attain multiband as well as broadband performances. Thus, the research work presented here in this thesis focuses on the design, simulation as well as testing of a stacked Sierpinski bow-tie antenna, and diamond shaped Sierpinski gasket fractal antenna. The research work starts with the review on fractal antennas, and then Sierpinski gasket bowtie antenna is designed using CST (Computer Simulation Software) microwave studio version 2017. This design is extended to a stacked structure (one layer of stacking) with three types of geometry namely: "driven and parasitic patches of same size", "parasitic patch smaller than driven patch", and "parasitic patch greater than the size of the given patch." The antennas are fed by utilising aperture coupled feeding mechanism because it provides reasonably higher bandwidth as compared to other feeds, and generates a moderate amount of spurious radiations. Stacked Sierpinski gasket fractal antenna with same active and parasitic patch covers the highest impedance bandwidth as compared to the other two geometries, and is therefore preferred. The obtained results are implemented on another design of stacked diamond Sierpinski gasket fractal antenna with similar dimensions of patches, which covers multiple resonant bands from 4.95 GHz to 5.04 GHz (90 MHz), 5.40 GHz to 6.72 GHz (1.32 GHz) and 6.95 GHz to 7.25 GHz (300 MHz). In order to validate the antenna application in practical wireless scenario, the two stacked structures with similar dimensions of driven and parasitic patch are fabricated by utilising photolithography process, and then tested on a VNA model no. E5063A. The measured results are quite matching with simulated ones allowing the antenna to be suitable for WLAN, UWB, G-band, E-band, radio communication, satellite communication, and radar communication applications.
Master of Engineering- Wireless Communication
Keywords: Fractal microstrip antenna; Sierpinski gasket; Bow-tie fractal antenna